Engineering T Cells Specific for a Dominant Severe Acute Respiratory Syndrome Coronavirus CD8 T Cell Epitope - Oh, Hsueh-Ling Janice (American Society for Microbiology, 2011)

(untitled)
Severe acute respiratory syndrome (SARS) is a highly contagious and life threatening disease, with a fatality rate of almost 10%. The etiologic agent is a novel coronavirus, severe acute respiratory syndrome coronavirus (SARS-CoV), with animal reservoirs found in bats and other wild animals and thus the possibility of reemergence. In this study, we first investigated at 6 years postinfection whether SARS-specific memory T cells persist in SARS-recovered individuals, demonstrating that these subjects still possess polyfunctional SARS-specific memory CD4(+) and CD8(+) T cells. A dominant memory CD8(+) T cell response against SARS-CoV nucleocaspid protein (NP; amino acids 216 to 225) was then defined in SARS-recovered individuals carrying HLA-B*40:01, a HLA-B molecule present in approximately one-quarter of subjects of Asian ethnicities. To reconstitute such a CD8(+) T cell response, we isolated the alpha and beta T cell receptors of the HLA-B*40:01-restricted SARS-specific CD8(+) T cells. Using T cell receptor gene transfer, we generated SARS-specific redirected T cells from the lymphocytes of normal individuals. These engineered CD8(+) T cells displayed avidity and functionality similar to that of natural SARS-specific memory CD8(+) T cells. They were able to degranulate and produce gamma interferon, tumor necrosis factor alpha, and macrophage inflammatory proteins 1α and 1β after antigenic stimulation. Since there is no effective treatment against SARS, these transduced T cells specific for an immunodominant SARS epitope may provide a new avenue for treatment during a SARS outbreak.